Fisheries Act 1985: conservation of fish in Malaysia / Mohamad Syafiq Abdul Aziz, Mohd. Azri Zorkarnini and Azri Naqiuddin Idris - Abdul Aziz, Mohamad Syafiq; Zorkarnini, Mohd. Azri; Idris, Azri Naqiuddin (2012)
This research paper is about the law on conservation of fish in Malaysia. The main Focus is on Fisheries Act 1985(Act 317). The goal of this socio-legal research is identify the problems and challenges with regards to conserving fish in Malaysia based on its legal aspect. This research has its core based on journal articles, books and earlier research conducted in relation with fisheries, and also interview from Department of Fisheries. After examining the sources, it is revealed that there still much to be done especially on part of enforcing of the law. In addition, this research highlights the importance of the need of comprehensive laws and the need of effective enforcement of law.